A new species of fringe-limb frog, genus Ecnomiohyla (Anura: Hylidae), from the Atlantic slope of Costa Rica, Central America - Savage, Jay M.; Kubicki, Brian (Zootaxa, 2010)
A new moderate-sized species of fringe-limb treefrog of the genus Ecnomiohyla is described from the Atlantic premontane slope of central Costa Rica. It differs primarily from other members of the genus in having the combination of cephalic and dorsal osteoderms, extensive digital webbing, a pointed prepollical bony projection in adult males, and the fleshy scalloped fringe on the hindlimb continuing across the heel. Additional material of the related but much larger species, Ecnomiohyla miliaria, is documented from localities of virtual sympatry for the two taxa. The presence or absence of sexually dimorphic male features: bony humeral projection, prepollical bony projection, and keratinized black spines on the thumb and prepollex are summarized for the ten members of the genus. Hyla tuberculosa, recently referred to the genus does not belong to this clade and is regarded as incertae sedis.